Update on the treatment options for canine hyperadrenocorticism. Issue 10 (17th December 2020) - Schofield, Imogen; Geddes, Rebecca; Fenn, Joe; Ramsey, Ian
Abstract : Background: Canine hyperadrenocorticism (or Cushing's syndrome) occurs due to a functional pituitary or adrenal tumour, resulting in excessive circulatory glucocorticoids, which produce the classical clinical signs in affected dogs. Although management of the disease traditionally focuses on treating these endocrine consequences, the pathology reflects an oncological disease with the possibility of progression of the underlying neoplasia. Surgical options for these tumours are now becoming increasingly available and successful. Aim of the article: This article covers how to distinguish between pituitary and adrenal hyperadrenocorticism as well as outlining the treatment options for this important disease in dogs.